Penggunaan Analytical Hierarchy Process dalam Pemilihan Strategi Digital Marketing untuk Pengembangan Usaha - Intan Oktaria; Doni Eko Hendro Pramono; Fathurrahman Kurniawan Ikhsan (Lembaga Pengembangan Kinerja Dosen, 2025)
Conventional marketing which is still predominantly carried out by female micro-entrepreneurs in Suka Mulya Village has limited market reach and low product selling value. This study aims to determine the most effective digital marketing strategy to increase the competitiveness of female MSME products using the Analytical Hierarchy Process (AHP) method. The four components of digital marketing explained are social media, marketplace, web platform, and social network. This study involved 30 respondents and used a paired comparison questionnaire. The results of the AHP calculation showed that social media had the highest weight preference of 53.88%, followed by marketplace (25.23%), web platform (14.64%), and social network (6.25%). The Consistency Ratio (CR) value of 0.033 (<0.1) indicates that the respondents' assessments are consistent and the calculation results are valid. These findings recommend a gradual digital marketing approach with an initial focus on social media, accompanied by ongoing training and mentoring. This study also contributes to the application of AHP for strategic decision making in the MSME sector.